Taming a monomeric [Cu(η6-C6H6)]+ complex with silylene12. Issue 18 (25th April 2018) - Parvin, Nasrina; Pal, Shiv; Echeverría, Jorge; Alvarez, Santiago; Khan, Shabana
Abstract : Realization of a hitherto elusive unsupported η 6 binding mode of benzene to a copper(i ) cation employing silylene as a ligand. The back-donation from Cu to Si(ii ) diminishes the repulsion between d-electrons and the benzene ring and enforces the η 6 binding mode. Abstract : Previous theoretical and experimental endeavors suggested that [Cu(C6 H6 )] + prefers the η 1 /η 2 mode over the η 6 mode due to the augmented repulsion between the benzene ring and metal d-electrons. Nevertheless, the use of silylene as a neutral ligand has led to the isolation of the first monomeric copper cation, [{PhC(N t Bu)2 SiN(SiMe3 )2 }Cu(η 6 -C6 H6 )] + [SbF6 ] − (3 ), where a copper atom is bound to the benzene ring in an unsupported η 6 fashion. However, the use of IPr (1, 3-bis(2, 6-diisopropylphenyl)imidazol-2-ylidene) in place of silylene results in the formation of [IPr·Cu(η 2 -C6 H6 )] + [SbF6 ] − (6 ), where the copper atom is bound to the benzene ring in the η 2 mode. The discrepancy in hapticities is also reflected when hexamethylbenzene is employed as the arene ring. The silylene supported copper cation continues to bind in the η 6 mode in2 while the NHC copper cation displays an η 3 bonding mode in5 . DFT calculations are carried out to understand how the use of silylene led to the η 6 binding mode and why IPr afforded the η 2 binding mode.